A Structural Empirical Model of Firm Growth, Learning, and Survival - Jaap H. Abbring; Jeffrey R. Campbell (Institute for the Study of Labor (IZA), 2003)
We present a structural model of firm growth, learning, and survival and consider its identification and estimation. In the model, entrepreneurs have private and possibly errorridden observations of persistent and transitory shocks to profit. We demonstrate that the model's parameters can be recovered from public observations of sales and survival, and we estimate them using monthly data from new bars in Texas. We find that entrepreneurs observe profit's persistent component without error. In this sense, their information is substantially superior to the public's.
Keywords: D83; C41; C34; C35; L11; 330; firm dynamics; Bayesian learning; identification; estimation; Unternehmenswachstum; Lernprozeß; Monopolistischer Wettbewerb; Schätzung; Gastronomie; Vereinigte Staaten